Phase I/II trial evaluating carbon ion radiotherapy for the treatment of recurrent rectal cancer: the PANDORA-01 trial - Combs, Stephanie; Kieser, Meinhard; Habermehl, Daniel; Weitz, Jürgen; Jäger, Dirk; Jäkel, Oliver; Büchler, Markus W.; Debus, Jürgen (BMC cancer, 2012)
Treatment standard for patients with rectal cancer depends on the initial staging and includes surgical resection, radiotherapy as well as chemotherapy. For stage II and III tumors, radiochemotherapy should be performed in addition to surgery, preferentially as preoperative radiochemotherapy or as short-course hypofractionated radiation. Advances in surgical approaches, especially the establishment of the total mesorectal excision (TME) in combination with sophisticated radiation and chemotherapy have reduced local recurrence rates to only few percent. However, due to the high incidence of rectal cancer, still a high absolute number of patients present with recurrent rectal carcinomas, and effective treatment is therefore needed.